Methodology for the treatment of the scientific-academic discourse from the teaching-learning process in pedagogical carrers - Bertha Miqueli Rodríguez; Yaumary Reiné Herrera (Universidade Federal do Norte do Tocantins, 2024)
The success of scientific communication depends, to a large extent, on the production of an efficient scientific-academic discourse; hence the importance of its treatment in the teaching-learning process of pedagogical careers. This topic constituted the starting point of the doctoral research of the main author of this article, which aims to propose a methodology that enables the improvement of the scientific-academic discourse in the teaching-learning process of the subjects of Exact Sciences and Natural. Theoretical, empirical and statistical-mathematical methods were used, which allowed the systematization of the theoretical references, the identification of the initial diagnosis, the development of the methodology and its validation by the criteria of specialists or experts and users. This methodology consists of objective, premises, foundations, stages and actions to be carried out by teachers and students as appropriate. The results achieved, from the validation carried out and the multidimensional correlation coefficient rpj with the application of the Cohaerentîa processing software, point to a fairly coherent criterion of the theoretical and methodological dimensions and coherent in the practical dimension. In the case of users, the criterion is coherent in the theoretical and practical dimensions and quite coherent in the methodological dimension, which gives internal consistency to the proposal made. With the use of the methodology aimed at the treatment of scientific-academic discourse, the development of the language and its functional components is favored.